Do parents still model news consumption? Socializing news use among adolescents in a multi-device world. (April 2018) - Edgerly, Stephanie; Thorson, Kjerstin; Thorson, Esther; Vraga, Emily K; Bode, Leticia
This study seeks to understand how American youth (aged 12–17 years) learn to consume the news, with specific concern for which devices (television, computer, tablet, and mobile phone) they employ in consuming news. Using a national survey of parent–child dyads, we explore (1) the role of demographics in creating a home environment supportive of news use, (2) the importance of parental modeling of news use via different media devices and whether the effect of modeling is complicated by the shift from shared to individualized media consumption, and (3) the impact of other socialization agents, such as peers and schools, in promoting youth news consumption above and beyond characteristics of the home. Results indicate that parental modeling remains an important factor in socializing news consumption, even when modeling takes place via mobile devices. Additionally, we find consistent evidence for "matched modeling" between the devices parents use for news and those used by youth.